Musculoskeletal pain syndrome in postpartum women - S Chungade, Niharika; Mahishale, Arati; Dalal, Anita; Angolkar, Mubashir (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aim: To estimate the occurrence of musculoskeletal pain syndrome in postpartum women. Method and Measures: A cross sectional study was conducted from August 2018 to February 2020 among 115 postpartum women attending at a tertiary care hospital in north Karnataka. Standardized and pre validated questionnaires “Brief Pain Inventory” and “Visual Analogue Scale” were used for subjective rating of pain. Result expressed in frequency and percentage. Results: Musculoskeletal pain syndrome was present among 99% women and most common complaint was low back pain (74%). General activity, walking ability and mood were much interfered by pain. Conclusions: The results showed there is high occurrence of musculoskeletal pain syndrome in postpartum women at a tertiary care hospital; most common is low back pain. Keywords: Brief Pain Inventory, musculoskeletal syndrome, postpartum women, Visual Analogue Scale.